Mudança organizacional : possibilidades e limites de um programa de capacitação e desenvolvimento organizacional - Cunha, Carlos Henrique Lisboa da (2005)
This research had as objective to evidence the potentialities and limitations of a qualification program and development for the change in organizations, from a study of case in a Metallurgy of great transport that it implanted, in the period of 1999 the 2002, a called program of change Movement of Qualification and Organizational Development (MCDO), in a process of intervention that included events of training, communicative actions, accompaniment of organizational climate, work of coaching and internal nets of sustentation. The change program was lead by a external consultant. In this direction, the investigated problem was: which the impacts provoked in an organization for one program of qualification and organizational development? The research was exploratory and essentially qualitative, with methodologists procedures that had included sources primary, with the application of the technique of focus groups, that it consisted of the accomplishment of meetings with two focal groups (leaderships and operational base of the organization), where had participated 26 employed ones. Also carried through documentary analysis as secondary source of data. It was possible to verify that the MCDO generated change in the human component of the organization, leaving an authoritarian model of management for a participativo model and adopting values and beliefs, as the respect to the people, the improvement of the communication and the internal relationship. Also, with the MCDO, it had the introduction of new practical of management of people. The company improved its financial pointers as the gross revenue and the profits, even so if cannot affirm direct relation with the implemented program of change. The MCDO did not affect strategical, structural components, politicians or technological, limiting it the informal components of the organization and this were one of its limitations.